Potential Role and Utilization of Plant Growth Promoting Microbes in Plant Tissue Culture - Soumare, Abdoulaye; Diédhiou, Abdala G.; Arora, Naveen Kumar; Tawfeeq Al-Ani, Laith Khalil; Ngom, Mariama; Fall, Saliou; Hafidi, Mohamed; Ouhdouch, Yedir; Kouisni, Lamfeddal; Sy, Mame Ourèye (Frontiers in Microbiology, 2021)
Plant growth promoting microbes (PGPMs) play major roles in diverse ecosystems, including atmospheric nitrogen fixation, water uptake, solubilization, and transport of minerals from the soil to the plant. Different PGPMs are proposed as biofertilizers, biostimulants, and/or biocontrol agents to improve plant growth and productivity and thereby to contribute to agricultural sustainability and food security. However, little information exists regarding the use of PGPMs in micropropagation such as the in vitro plant tissue culture. This review presents an overview of the importance of PGPMs and their potential application in plant micropropagation. Our analysis, based on published articles, reveals that the process of in vitro classical tissue culture techniques, under strictly aseptic conditions, deserves to be reviewed to allow vitroplants to benefit from the positive effect of PGPMs. Furthermore, exploiting the potential benefits of PGPMs will lead to lessen the cost production of vitroplants during micropropagation process and will make the technique of plant tissue culture more efficient. The last part of the review will indicate where research is needed in the future.